1986
DOI: 10.1063/1.865786
|View full text |Cite
|
Sign up to set email alerts
|

Microbubble skin friction reduction on an axisymmetric body

Abstract: A reduction in skin friction drag is shown when gas is introduced into the liquid turbulent boundary layer of a submerged axisymmetric body. The 89 mm diameter, 632 mm long body has a cylindrical balance 273 mm long. Free stream speeds in the 305 mm diameter tunnel are as high as 17 m/sec, giving length Reynolds number of up to 10 million. In general, skin friction reduction is shown to increase with increasing free stream speed. At high speeds, helium injection is shown to be more effective at reducing skin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…Hence, for those etched surfaces, water molecules could not directly contact the surface of the fluoropolyurethane, and these surface characteristics could reduce the friction factor. As for continuously increasing the Reynolds number and flow rate, the non-shear air-water interface might become thinner and thinner [45,46]. However, the superhydrophilic drag reduction effect was even more obvious than the superhydrophobic.…”
Section: Microchannel Drag-reduction Analysismentioning
confidence: 99%
“…Hence, for those etched surfaces, water molecules could not directly contact the surface of the fluoropolyurethane, and these surface characteristics could reduce the friction factor. As for continuously increasing the Reynolds number and flow rate, the non-shear air-water interface might become thinner and thinner [45,46]. However, the superhydrophilic drag reduction effect was even more obvious than the superhydrophobic.…”
Section: Microchannel Drag-reduction Analysismentioning
confidence: 99%
“…Their data showed that BDR improved with decreasing flow speed, increasing gas injection rates, and when buoyancy assisted in retaining the bubbles in the boundary layer. Deutsch & Castano (1986) studied BDR on an axisymmetric body that was 0.089 m in diameter and 0.62 m in total length for Re L < 10 7 and gas injection rates corresponding to 0 <ᾱ < 1. They showed that drag reduction improved with increasing Fr as the influence of buoyancy was reduced and the bubbles stayed closer to the surface of the body.…”
Section: Experimental Observation Of Bubble Drag Reduction With Gas Imentioning
confidence: 99%
“…This pioneering work was followed by several experimental investigations conducted in the former Soviet Union (9), (10) where they reported a significant drag reduction in water tunnel boundary layers by injection of air bubbles through porous plates. In the 1980s, through a series of systematic studies in water tunnels, the drag reduction on a flat plate due to micro-bubbles generated by porous plates (11) -(14) and on axisymmetric body by circumferential porous rings (15) - (17) , were observed with values up to 80%. More recently, several investigations of a flat plate tunnel boundary layer were carried out to study the effect of bubble size and bubble concentration on the reduction of skin friction (18) - (26) .…”
Section: Introductionmentioning
confidence: 99%